Asuhan Keperawatan Medikal Bedah pada Ny. R dengan Diabetes Mellitus Tipe II di RSUD Prof. H. Muhammad Yamin Pariaman - Nisa Marchanda; Aulia Asman; Kheniva Diah Anggita; Linda Marni (CV. ITTC INDONESIA, 2026)
Type II Diabetes Mellitus is a chronic health disorder characterized by an increased blood glucose level due to the pancreas being unable to produce insulin hormone according to the body's needs. At RSUD M. Yamin Pariaman, Type II Diabetes Mellitus ranks third among the ten most common diseases. This study aims to provide nursing care to patients with Type II Diabetes Mellitus in the internal medicine ward at RSUD M. Yamin Pariaman. The case study subject is Mrs. R, who was admitted on February 1, 2026. The methods used include direct observation, physical examination, interviews, and documentation. The nursing problems identified include blood glucose level instability, nutritional deficit, and sleep pattern disturbances. Evaluation results showed that blood glucose level instability, nutritional deficit, and sleep pattern disturbances were fully resolved after 5 days of implementation, and the patient was discharged on February 6, 2026.